2013
DOI: 10.1016/j.jacc.2013.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary Compared With Intravenous Bolus Abciximab Application During Primary Percutaneous Coronary Intervention in ST-Segment Elevation Myocardial Infarction

Abstract: This largest multicenter CMR study in ST-segment elevation myocardial infarction patients to date demonstrates no benefit of intracoronary versus intravenous abciximab administration on myocardial damage and/or reperfusion injury. Infarct size determined by CMR was significantly associated with major adverse cardiac events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
121
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 166 publications
(136 citation statements)
references
References 21 publications
3
121
3
3
Order By: Relevance
“…In contrast, the shock 925 Shock Index and Myocardial Damage significant difference in CMR markers of myocardial damage between both groups. 22 For the purpose of the current analysis, only patients with recorded admission heart rate and admission systolic blood pressure were eligible (n=791, 99.5%). Patient characteristics, including blood pressure and heart rate, were systematically assessed according to a predefined study protocol.…”
mentioning
confidence: 99%
“…In contrast, the shock 925 Shock Index and Myocardial Damage significant difference in CMR markers of myocardial damage between both groups. 22 For the purpose of the current analysis, only patients with recorded admission heart rate and admission systolic blood pressure were eligible (n=791, 99.5%). Patient characteristics, including blood pressure and heart rate, were systematically assessed according to a predefined study protocol.…”
mentioning
confidence: 99%
“…Based on the in-and exclusion criteria of this multicenter clinical trial as well as the treatment of patients in specialized highvolume centers, our results might not be generalizable to all STEMI populations. Although AIDA STEMI was designed as all-comers trial to represent a "real-world" STEMI population [18,20], further confirmation of our findings in other studies would be important. It is, however, important to note that the power of our study to exclude a 3 % difference in infarct size or LV ejection fraction between groups was approximately 95 %.…”
Section: Limitationsmentioning
confidence: 59%
“…The rationale, design and main results of AIDA STEMI as well as its CMR substudy have been reported elsewhere [15,[17][18][19][20]. Briefly, AIDA STEMI randomized 2065 consecutive STEMI patients treated within 12 h after symptom onset to either intracoronary or intravenous abciximab bolus (0.25 mg/kg) during PPCI with a subsequent 12 h dose-adjusted intravenous infusion.…”
Section: Study Design and Populationmentioning
confidence: 99%
See 2 more Smart Citations